The status of glucocorticoid-induced leucine zipper protein in the salivary glands in Sjögren's syndrome: predictive and prognostic potentials. Issue 1 (December 2015) - Qin, Xu; Liu, Jun; Abdelsayed, Rafik; Shi, Xingming; Yu, Jack; Mozaffari, Mahmood; Baban, Babak
Abstract Background We recently showed that an imbalance between the pro-inflammatory cytokine, interleukin (IL)-17, and the developmental endothelial locus-1 (Del-1) likely contributes to inflammation and salivary gland abnormalities in Sjögren's syndrome (SS). The glucocorticoid-induced leucine zipper (GILZ) protein is a pivotal player in mediating the anti-inflammatory effects of glucocorticoids. However, its status and role in salivary gland inflammation and dysfunction in SS are not established. Thus, we tested the hypothesis that SS is associated with reduced GILZ expression, thereby contributing to Del-1/Il-17 imbalance and inflammation in salivary glands. Methods We utilized the nonobese diabetic (NOD) mice, a model of SS-like disease as well as lower-lip biopsy samples of subjects without or with a diagnosis of SS in association with immunostaining studies. These studies were complemented with in vitro and flow-cytometry studies whereby interleukin (IL)-23-treated salivary gland cells were co-cultured with GILZ-expressing cells or control cells; IL-23 is known to increase generation of IL-17. Results Salivary glands of NOD mice displayed marked leukocyte infiltration and reduced GILZ expression in association with increased IL-17 but decreased Del-1 expression. A similar pattern was observed for lower-lip biopsy samples of SS than non-SS subjects. Further, IL-23-treated salivary gland cells displayed marked increase in IL-17 but reduced Del-1 positive cells which were reversed with co-culturing with GILZ-expressing cells but not control cells. Collectively, the results are suggestive of dysregulation of GILZ playing a role in inflammation and associated Del-1/Il-17 imbalance in SS. Conclusions Complementing our demonstration of Del-1/IL-17 imbalance in salivary glands in SS, the present study has established the relevance and significance of GILZ as a novel predictive and prognostic molecular fingerprint for SS. Thus, assessment of minor salivary gland GILZ expression, in conjunction with Del-1/IL-17 imbalance, could potentially offer a more sensitive approach to help with diagnosis of SS, at early stage of the disease, than that based on leukocyte infiltration. Future studies should establish whether treatment with GILZ ameliorates signs and symptoms of salivary malfunction of SS for which effective treatment options remain elusive.